2021
DOI: 10.1186/s12978-021-01148-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of uterine fundal pressure during the second stage of labour for women giving birth in health facilities: a systematic review and meta-analysis

Abstract: Background Uterine fundal pressure involves a birth attendant pushing on the woman’s uterine fundus to assist vaginal birth. It is used in some clinical settings, though guidelines recommend against it. This systematic review aimed to determine the prevalence of uterine fundal pressure during the second stage of labour for women giving birth vaginally at health facilities. Methods The population of interest were women who experienced labour in a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The results of our study showed that 60.8% of the providers did not consider the application of fundal pressure during delivery as a form of mistreatment. Based on the available evidence, the use of fundal pressure during vaginal birth is very common in hospitals [43][44][45][46][47][48]. A systematic review showed that the prevalence of fundal pressure ranged from 0.6 to 69.2% globally [45].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed that 60.8% of the providers did not consider the application of fundal pressure during delivery as a form of mistreatment. Based on the available evidence, the use of fundal pressure during vaginal birth is very common in hospitals [43][44][45][46][47][48]. A systematic review showed that the prevalence of fundal pressure ranged from 0.6 to 69.2% globally [45].…”
Section: Discussionmentioning
confidence: 99%
“…The authors therefore recommend guidelines and recommendations on which manoeuvre techniques can be used and under what circumstances. Because fundal pressure is not beneficial to women and is potentially harmful, the WHO and other bodies strongly advise against it ( 26 – 28 ). Ferrington et al ( 26 ) examined 76 studies from 22 countries and found that uterine fundal pressure is still widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Because fundal pressure is not beneficial to women and is potentially harmful, the WHO and other bodies strongly advise against it ( 26 – 28 ). Ferrington et al ( 26 ) examined 76 studies from 22 countries and found that uterine fundal pressure is still widespread. More efforts are needed to prevent the potentially unnecessary and harmful management, they said.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of MFP is not recommended in current WHO/FIGO and several guidelines, the procedure is still utilized to assist vaginal delivery and avoid unnecessary cesarean sections due to various fetal or maternal problems 2–4 . According to a latest systematic review and meta‐analysis, a pooled prevalence of MFP was still 23.2% and the highest prevalence of MFP (34.7%) was reported in the lower‐middle countries of income level 5 . In Japan, MFP‐assisted vaginal deliveries account for 9.5% of all vaginal deliveries 6 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] According to a latest systematic review and meta-analysis, a pooled prevalence of MFP was still 23.2% and the highest prevalence of MFP (34.7%) was reported in the lowermiddle countries of income level. 5 In Japan, MFPassisted vaginal deliveries account for 9.5% of all vaginal deliveries. 6 There is insufficient evidence that MFP is beneficial to neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%